2014
DOI: 10.1055/s-0033-1363466
|View full text |Cite
|
Sign up to set email alerts
|

Möbius Syndrome: Misoprostol Use and Speech and Language Characteristics

Abstract: Introduction Möbius syndrome (MS; VI and VII palsy) is a rare disease that in Brazil has a great frequency because of the use of misoprostol during pregnancy. Objective Verify if the speech and language performance of children with MS whose mothers reported use of misoprostol (Cytotec, Pfizer, Connecticut, USA) are different from the performance of children of mothers who did not report use. Methods The stomatognathic system beyond receptive and expressive language and speech was evaluated in children with MS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…Moebius syndrome is a rare, non-progressive disease, characterized by the paralysis of the facial nerve, mostly bilateral, sixth nerve palsy, and it may be associated with injury and other cranial, thoracic abnormalities, and limbs, dental problems, malformation of the tongue and cleft palate (34). The main features are: lack of facial expression; convergent strabismus; inadequate tongue mobility; micrognathia; suction, chewing, swallowing and speech irregularities; clubfoot; syndactyly (35) . There are several types of treatment for facial paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moebius syndrome is a rare, non-progressive disease, characterized by the paralysis of the facial nerve, mostly bilateral, sixth nerve palsy, and it may be associated with injury and other cranial, thoracic abnormalities, and limbs, dental problems, malformation of the tongue and cleft palate (34). The main features are: lack of facial expression; convergent strabismus; inadequate tongue mobility; micrognathia; suction, chewing, swallowing and speech irregularities; clubfoot; syndactyly (35) . There are several types of treatment for facial paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies have shown a strong correlation between misoprostol usage and Moebius Syndrome, which has been reliably corroborated by decades of research. 14,34 Furthermore, one key factor supporting this view is that the affected structures commonly originate between 23 to 46 days of embryonic life, suggesting the embryologic origin of Moebius Syndrome might be a stronger overall argument as this is also the period in which teratogenesis affects the embryo the most.…”
Section: Etiologymentioning
confidence: 99%
“…In Brazil, the majority of the cases of MS were related to the exposure to misoprostol in failed attempts of abortion. [5][6][7][8] Palsy of cranial nerves VI and VII can lead to movement deficits in the muscles of facial expression, mastication, and eyelids. In addition to these features, one can observe hypotonia, deafness, ear anomalies, and strabismus.…”
Section: An Interesting Case Of Systemic Lupus Erythematosus In a Patmentioning
confidence: 99%
“…Interruption of blood supply of subclavian arteries during embryogenesis is the most accepted theory to explain the etiopathogeny of the syndrome, as it would induce romboencephalic malformation between the sixth and eight week of gestation, thus resulting in the MS phenotype. In Brazil, the majority of the cases of MS were related to the exposure to misoprostol in failed attempts of abortion …”
Section: Introductionmentioning
confidence: 99%